Persepsi Generasi Muda Tentang Pertanian Organik san Pengaruhnya Terhadap Minat Berwirausaha - Febrinda Annisa Munandar; Bayu Krisnamurthi; Burhanuddin Burhanuddin (Forum Agribisnis, 2023)
The number of farmers that continues to decline is one of the problems that occur in the agricultural sector. The interest to become a farmer or business actor in agriculture, especially for the younger generation also tends to decline. They perceive that it is more tiring to work in the agricultural sector because they work outdoors. By administering a survey to 63 members of Komunitas Petani Muda Indonesia, this research aimed to determine the opinions of the younger generation about organic farming and their impact on entrepreneurial goals. The technique of collecting samples employs probability sampling, descriptive analysis, and SEM-PLS. The results show that the knowledge and positive views about organic farming affect the interest in entrepreneurship, However, their interest in organic farming tends to be low. Several factors contribute to this, including the fact that many individuals who do not understand organic products equate the price of organic products with conventional agricultural products and the difficulty of marketing organic products. The conclusion is that perception influences the desire of young people to become entrepreneurs.